A forsaken prophecy - McEwan, Stacey (McEwan, Stacey. Artisan trilogy, 2026)
"In Belavere Trench, the Artisans and the Craftsmen are at war. Patrick, the last Alchemist, and Nina, the world's only known earth Charmer, have been captured by the Artisans, putting Patrick's rebel union in a precarious position. Though he hasn't forgiven Nina her betrayals, Patrick has other things to worry about. He is finally reunited with his father, a prisoner of the Artisans, and the group lands a narrow escape only with the help of Nina's first love, Theo. Decoding an ancient prophecy, they set off in search of an infinite supply of idium that will determine the course of the war, should it prove more than a myth. Fleeing across Craftsman towns on the brink, they will encounter old friends--and enemies--in search of answers."--